(untitled) (Jurnal Intek Akuakultur, 2018)
This research was done on March 2 to 5, 2018 in Desa Pengujan, Bintan Bay II, Bintan Regency. The purpose of this research was to knew the best temperature treatment for development of silver pompano larvae. This research were used Completely Randomized Design (CRD) there were, A (28°C), B (30°C), C (32°C) and D (34°C) with 3 replications in each treatment. The results showed that A treatment (32°C) had the best yolk volume shrinkage was 84.432.467,5 µm3 and the best of egg yolk absorption rate was 4.690.692,6 µm3/jam.